Long-term monitoring of metal pollution by urban trees - Gratani, Loretta; Crescente, Maria Fiore; Varone, Laura (Atmospheric Environment, 2008)
The atmospheric pollution level in Rome was monitored in the year 2006. Five sites in the historical centre were considered. The concentration of Al, Fe, Cu, Zn, and Pb was analysed in washed and unwashed Quercus ilex leaf samples. Moreover, in order to verify the changes in atmospheric pollution in the historical centre of the city after the introduction of the limited trafﬁc zone (LTZ), previous data collected in the years 1979 and 1996 were also considered. The leaf’s internal concentration of Al, Fe, Cu, Zn, and Pb was 28, 22, 40, 77 and 37%, respectively, of the total concentration, and it was in the same range monitored in the years 1979 and 1996. The results underlined a signiﬁcant (p < 0.05) decreasing of metal concentration on unwashed leaves with on an average 92%, compared to ones monitored in the year 1979. The mean value of the total trafﬁc ﬂow during the limitated period (Monday to Friday, from 6:30 a.m. to 6:00 p.m, and Saturday from 2:00 to 6:00 p.m.) was 75.000 vehicles, compared to 90.000 ones before the electronic gates were activated; moreover, a 15% decrease in the daily trafﬁc peak (8:30–9:30 a.m) was monitored. The metal concentration in Q. ilex leaves was be related to motor vehicle emissions, conﬁrmed also by PCA. The data obtained on the leaf metal concentration trend in Rome, over a period of 27 years, underlined the importance of the City Council provisions. These results conﬁrmed the use of Q. ilex for long-term monitoring of metal concentration in those urban areas where the species was naturally present, and widely distributed in the landscape.
Keywords: Bio-monitor; Metal pollution; Quercus ilex; rome; Vehicular trafﬁc

Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal - Fernandes, J C; Henriques, F S (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.
Keywords: acorns; holm oak (voyant); leaves; Metal pollution

Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal - Fernandes, J. C.; Henriques, F. S. (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.
Keywords: acorns; holm oak (voyant); leaves; Metal pollution